ANALYSIS OF COPYRIGHT OF SILVERWARE MOTIVE DESIGN AT CELUK, SUKAWATI, GIANYAR, BALI - Lodra, Dr. I Nyoman (IJRDO- Journal of Educational Research, 2016)
The infringement as meant is the plagiarism of silver motif design which belongto foreign businessmen that brought local designers so the case to Denpasar court. TheAmerican entrepreneurs who has silver businesses in Baturening, Mambal, Badung,claimed that the design motifs used by local craftsmen silver in Celuk, Sukawati,Gianyar, Bali imitated the designs created by him. The local craftsmen create the designsthrough creative process by setilir of the Balinese values. The creation process resultingintellectual treasures with novelty is believed to be recognized and receive copyright. sothe local designers can be freed from worrisome of working under fearsome that they willviolate the copyright. The background of the creation process in obtaining the copyrightcan be formulated as follows: (1) how the process of creating silver motif design is ableto obtain a copyright, (2) how the concept of creating Celuk silver motif design, (3) howthe criteria of Celuk silver motif design related to Copyright. From the background of thethe problems, this study has objectives: (1) knowing the process of creating Celuk silvermotif design, (2) determining the concept of creating Celuk silver, and (3) determiningthe copyright criteria in designing Celuk silver motif. The research methodology used inthis study is descriptive qualitative using iconology, ethnography, and cultural approachwith the perspective of the Copyright Act.